Understanding the Needs of Young People Who Engage in Self-Harm: A Qualitative Investigation - Hetrick, Sarah E.; Subasinghe, Aruni; Anglin, Kate; Hart, Laura; Morgan, Amy; Robinson, Jo (Frontiers in Psychology, 2020)
Self-harm is common and associated with adverse outcomes. Research about the risk factors for self-harm has informed the field with regard to clinical interventions that should be delivered for young people who engage in self-harm. Missing is an in-depth understanding of what the triggers of an urge to self-harm might be, including in young people being treated with a clinical intervention. Therefore, there little knowledge about what techniques young people find helpful to deal with urges to self-harm when they occur. This qualitative study engaged seven young people with lived experience of self-harm in semi-structured interviews about the immediate triggers of the urge to self-harm, and helpful strategies to manage this urge. Thematic analysis using a general inductive approach revealed distressing emotions and a sense of isolation as key and interrelated themes, with other triggers associated with their induction. Highlighted was the wide range of situations and emotions that can be triggering, such that a further key theme was the idiosyncratic nature of the self-help strategies young people found helpful. Intervention that are developed to support young people who self-harm must address this complexity and highlights the need for young people to maintain some autonomy and control while being supported to connect with others for support. This research adds to the literature on self-help strategies to support young people in moments when they are experiencing distressing emotions, feel isolated and have an urge to self-harm providing important insight to the prevention and intervention in self-harm among young people.